Brain-derived neurotrophic factor prevents LPS-induced dysregulation of GABAergic interneuron markers in mouse hippocampus - Rezaei, Sara; Banasr, Mounira; Prevot, Thomas D.; Bansal, Yashika; Vieira, Erica; Sibille, Etienne (Frontiers in Cellular Neuroscience, 2025)
BackgroundInflammation causes reduced markers of GABAergic interneurons and brain-derived neurotrophic factor (BDNF) in the hippocampus, features often associated with neuropsychiatric disease pathophysiology. However, the mechanism connecting inflammation to GABAergic markers remains unclear. We hypothesized that reduced BDNF mediates the effects of LPS on GABAergic markers and that hippocampal BDNF infusion would prevent LPS-induced reduction in somatostatin (SST), and coexpressed markers, including cortistatin (CORT), and neuropeptide Y (NPY).MethodC57BL/6 mice (n = 14; 12–14 weeks old; 50% female) received intracerebral administration of BDNF (250 ng) or vehicle control in the hippocampus via stereotaxic surgery (unilateral). Thirty minutes after BDNF administration, intraperitoneal injection of LPS (2 mg/kg) or phosphate buffered saline (PBS) was performed and mice were euthanized 18 h post LPS-injection. The hippocampus was collected for investigation of cellular markers using quantitative PCR and enzyme-linked immunosorbent assay (ELISA).ResultsLPS administration in mice that did not receive pre-treatment with BDNF led to a significant reduction in mRNA levels of Bdnf (p = 0.0049), Sst (p = 0.0416), Npy (p = 0.0088), and Cort (p = 0.0055). BDNF infusion into the hippocampus prior to LPS injection prevented the reduction in Bdnf, Sst, and Cort mRNA expression. BDNF also prevented the LPS-induced effect on protein levels of BDNF, SST and NPY. BDNF prevention of LPS effects occurred in the context of sustained elevation of inflammatory markers (interleukin 1-beta and glial fibrillary acidic protein).ConclusionBDNF may protect SST GABAergic interneurons from LPS-induced inflammation, providing novel insights into the molecular mechanisms linking inflammation and GABAergic dysfunction in neuropsychiatric diseases.